Geochemical features of hydrothermal systems in Jujuy Province, Argentina: Hints for geothermal fluid exploration. (August 2020) - Peralta Arnold, Yésica; Franco, M. Gabriela; Tassi, Franco; Caffe, Pablo J.; Jofre, Cynthia B.; Claros, Marcelo; Villalba Ulberich, Juan P.; Rizzo, Andrea L.; Cabassi, Jacopo
Abstract: Fluid primary source(s) and chemical-physical processes controlling water and gas chemistry of thermal springs from Eastern Cordillera, sub-Andean Ranges and Santa Bárbara (Jujuy Province, northern Argentina) were investigated to provide information for a preliminary evaluation of the geothermal potential in these areas. Thermal manifestations in Eastern Cordillera (Reyes) and part of those in the western sector of sub-Andean Range (Aguas Calientes) are fed by shallow aquifers, interacting with Quaternary- Neogene rocks and the upper portion of Pliocene-Miocene formations (Orán Group), whereas the meteoric water recharge area is located at >2500 m a.s.l., corresponding to Chañi hill. Differently, El Jordán thermal spring in the sub-Andean Range is fed by a hydrothermal aquifer hosted within highly porous and fractured formations of the Salta Group (Yacoraite Formation) and recharged by meteoric water from Sierra de Calilegua (∼1500 m a.s.l.). The latter is the recharge area of the La Quinta geothermal waters as well, but these have been fed at higher altitudes (>2500 m a.s.l.) in the range. The hydrothermal reservoir feeding the other thermal springs from the Santa Barbara system (Caimancito, El Palmar, and Siete Aguas) is recharged by meteoric water from Zapla Ranges and Santa Barbara Hill at <2500 m a.s.l. The high-TDS (>16, 000 mg/L) Na + -Cl - La Quinta thermal springs are produced by interaction with the evaporite deposits of Salta Group, including halite, whereas the chemistry of El Palmar, El Jordán and Caimancito thermal springs, showing a Na + -SO4 2- (Cl − ) composition, depends on mixing with shallower SO4 2- -rich waters interacting with gypsum deposits of Anta Formation. Dissolved and bubbling gases from all the investigated provinces are related to CO2 - and CH4 -rich crustal fluids produced by both thermogenic processes occurring within the hydrothermal systems and microbial activity at relatively low depth, with low to negligible mantle contribution, as indicated by the 3 He/ 4 He values ≤ 0.21 Ra. The fluid reservoir feeding the Quinta thermal springs shows the highest estimated temperatures (>200 °C), which, considering the depth of Salta Group in the Santa Barbara system (~2000 m), support the idea, suggested by previous authors, of an anomalous geothermal gradient for this area, a promising pre-requisite for future exploitation of the geothermal resource. Highlights: Thermal springs from three geologic domains in Jujuy Province were investigated. Uprising hydrothermal fluids were controlled by local and regional tectonics. The deepest hydrothermal reservoir in Santa Barbara (SB) system hosts Na–Cl waters. Estimated temperature of the fluid reservoir from SB is > 200 °C. The occurrence of an anomalous geothermal gradient is confirmed in SB.